Cegah Hipertensi dan Diabetes Melitus: Upaya Edukasi MasyarakatPesisir Desa Sampuabalo, Kabupaten Buton - Hikmawati, Hikmawati; Samsuddin, Samsuddin; Muhsinah, Siti (PT Karya Inovasi Berkelanjutan, 2025)
Sustainable Development Goals (SDGs) Achievement The community service activity reported in this article aims to raise awareness and enhance public understanding of non-communicable diseases (NCDs), specifically hypertension and diabetes mellitus. This initiative aligns with Sustainable Development Goal (SDG) 3, which seeks to ensure healthy lives and promote well-being for all at all ages. Furthermore, this program directly contributes to Target 3.4 of the SDGs, which aims to reduce premature mortality from non-communicable diseases by one-third by 2030 through prevention and treatment, as well as promote mental health and well-being.